Efektivitas Massase Anak Prasekolah terhadap Status Gizi - Syuhrotut Taufiqoh (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2021)
Objective: One indicator in determining a child's health is nutritional status. Good nutritional status can help the process of optimal growth and development of children. Handling malnutrition status can be done by giving the baby a balanced dietary intake through the mother by providing exclusive breastfeeding and baby massage, which the parents can do. This study aimed to determine the effectiveness of preschoolers' massage on nutritional status.Methods: This research is in the form of Quasy Experimental using pre-test and post-test. The sampling technique uses accidental sampling. This research was conducted at PAUD 'Aisyiyah Sidotopo Wetan Surabaya in November 2021. This study examined massage (independent variable) and nutritional status (dependent variable). Nutritional status is an indicator in determining a child's health status by filling out the Towards Healthy Card (KMS), with poor and good categories. Massage for preschool children is a massage for children aged 3-6 years who are experiencing good nutrition and malnutrition. This massage was measured through observation, with the measurement results not being massage therapy and massage therapy. Data collection in this study used primary data, namely data collection obtained through direct interviews with the child's mother using interviews and observation. Data were analyzed by Paired sample test.Results: The results of the study showed the effectiveness of massage on the nutritional status of preschoolers. The Wilcoxon Mann-Whitney statistical test showed a significant p-value of 0.01 (p <0.05)Conclusion: This study concludes that massage is effective on nutritional status in preschool children. Health workers, especially midwives as providers of maternal and child health services, are expected to socialize by giving massage therapy.